CD45RO+ memory T-cells produce IL-17 in patients with atherosclerosis - Behnamfar, N; Zibaeenezhad, M J; Golmoghaddam, H; Doroudchi, M (Cellular and Molecular Biology, 2015)
Several CD4+ T helper (Th) cell subsets are shown to play a role in atherosclerotic lesion formation and progression. We investigated the frequencies of IL-17 and IFN-Î³ producing CD4+ T-cell subsets in the peripheral blood mononuclear cells (PBMCs) of 10 patients with atherosclerosis and 6 individuals with normal/insignificant coronary artery disease. Th1 and Th17 memory and effector T-cells were enumerated by flowcytometry and correlated with the clinical data and lipid profiles of the subjects. We found the ex-vivo (P=0.0001) and in-vitro production of IL-17 (P=0.001) but not IFN-Î³ by CD4+ memory T-cells of patients. CD45RO+ memory cells were the major producers of IL-17 and the CD4+CD45RO+PD-1- T-cells of the patients produced higher levels of IFN-Î³ than controls (P=0.02). Positive correlations between the frequency of CD4+CD45RO+IL-17+IFN-Î³- T-cells and serum LDL-C (P=0.007), triglyceride (P=0.02), and systolic (P=0.001) and diastolic (P=0.009) blood pressures (BP) were found. The frequency of CD4+CD45RO+IL-17-IFN-Î³- T-cells, which was higher in controls than patients, showed negative correlations with the serum LDL-C (P=0.01) and triglyceride (P=0.02) levels and systolic (P=0.003) and diastolic (P=0.01) BPs. The ex-vivo Th17 deviation of memory T-cells in atherosclerosis and high PD-1 expression are associated with the correlates of atherogenesis such as LDL, TG, and BP.